Thriving in academia : building a career at a teaching-focused institution - Ansburg, Pamela I.; Basham, Mark E.; Gurung, Regan A. R. (American Psychological Association, 2022)
"Veteran professors synthesize their combined 60+ years of expertise at primarily undergraduate, teaching-focused universities into easy-to-follow advice for graduate students and current faculty seeking to build thriving careers at similar institutions. Writing in a friendly tone that includes their personal reflections, the authors guide readers through the entire career trajectory: finding and applying for positions, developing essential knowledge and skills over the course of one's career, seeking tenure and promotions, and continuing to thrive in the mid- to late-career stages while preparing for retirement. The authors offer detailed insights for becoming a successful academic who can meet all the expectations of a teaching-focused institution. They explain how to develop core teaching competencies; choose advising philosophies for mentoring individual students, groups, and clubs; perform high-quality faculty service; and achieve scholarly, creative, and research goals-all while managing a high teaching load. Strategies for obtaining scarce yet crucial resources-time, money, and mentors-are also provided"--